Kualitas Pelayanan Publik Secara Daring Pada Masa Pandemi Covid-19 di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bekasi - Widya Tria Ningrum; Haura Atthahara; Ani Nurdiani Azizah (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study examines the quality of online public services during the Covid-19 pandemic at the Bekasi Regency Population and Civil Registration Service using the theory of public service quality according to Zeithaml, Parasuraman and Berry in (Hardiansyah, 2018) with five dimensional variables which include physical evidence, reliability, responsiveness, assurance and empathy. This study used descriptive qualitative method. The data collection technique was carried out through triangulation which included interviews, observations and documentation studies, then the data that had been obtained were analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The results of the research and discussion show that public services during Covid19 carried out by the Bekasi Regency Population and Civil Registration Service have been running optimally in every dimension.